2008
DOI: 10.1523/jneurosci.3625-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Kainate Modulates Presynaptic GABA Release from Two Vesicle Pools

Abstract: Inhibitory control of local neuronal circuits is critical for prefrontal cortical functioning. Modulation of inhibitory circuits by several neuromodulators has been demonstrated, but the underlying mechanisms are unclear. Neuromodulator effects on synaptic vesicle recycling have received little attention. Controversy also exists whether different pools of synaptic vesicles underlie spontaneous and activity-dependent vesicle recycling. We therefore investigated the effects of kainate receptor activation on GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
67
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 58 publications
4
67
1
Order By: Relevance
“…While there still could be conditions that favor (in a limited way) some bias toward how synaptic vesicles form following one type of stimulation, and how they are later released, our results indicate that there is no strict segregation between vesicles used for evoked and spontaneous release. This conclusion disagrees with some of the previously published works 6,[8][9][10] . The source of this discrepancy is not completely clear, although pitfalls of the data analysis methods used in some of the previous studies have already been pointed to 7 .…”
contrasting
confidence: 98%
See 4 more Smart Citations
“…While there still could be conditions that favor (in a limited way) some bias toward how synaptic vesicles form following one type of stimulation, and how they are later released, our results indicate that there is no strict segregation between vesicles used for evoked and spontaneous release. This conclusion disagrees with some of the previously published works 6,[8][9][10] . The source of this discrepancy is not completely clear, although pitfalls of the data analysis methods used in some of the previous studies have already been pointed to 7 .…”
contrasting
confidence: 98%
“…Surprisingly, both of these findings have been later contested in similar experiments -FM dyes taken up either at rest or during stimulation could be released with identical kinetics, and the inhibition of reacidification during depolarization led to a cessation of spontaneous release 7 (see also 5 ). However, later studies have again found different FM dye release kinetics when using different loading paradigms 8,9 , and labeling experiments using the expression of a biotinylated variant of the synaptic vesicle marker VAMP2 (synaptobrevin) also supported the hypothesis that spontaneously and actively recycling vesicles are different 10 .We tested here this controversial issue by combining several fluorescence imaging assays. We sought to reproduce the FM dye loading/unloading paradigms used in the past.…”
mentioning
confidence: 84%
See 3 more Smart Citations